2016
DOI: 10.1017/jog.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the evolution of the Juneau Icefield between 1971 and 2100 using the Parallel Ice Sheet Model (PISM)

Abstract: ABSTRACT. We study the evolution of the Juneau Icefield, one of the largest icefields in North America (>3700 km 2 ), using the Parallel Ice Sheet Model (PISM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(95 citation statements)
references
References 52 publications
(95 reference statements)
2
92
1
Order By: Relevance
“…Starting from ice-free conditions, Hardangerjøkulen grows to only 20 % of its present-day volume under a modern climate. This is in stark contrast to the Juneau Icefield in Alaska, an ice field in a similar climatic setting, which in model simulations regrows close to modern ice volume under present-day mass balance conditions (Ziemen et al, 2016). The authors attribute this insensitivity to initial conditions to the complex topography of the Juneau Icefield, with numerous outlet glaciers able to retreat up to high altitudes where positive mass balance areas persist even under future warming scenarios.…”
Section: Mass Balance Sensitivity and Hysteresismentioning
confidence: 81%
See 1 more Smart Citation
“…Starting from ice-free conditions, Hardangerjøkulen grows to only 20 % of its present-day volume under a modern climate. This is in stark contrast to the Juneau Icefield in Alaska, an ice field in a similar climatic setting, which in model simulations regrows close to modern ice volume under present-day mass balance conditions (Ziemen et al, 2016). The authors attribute this insensitivity to initial conditions to the complex topography of the Juneau Icefield, with numerous outlet glaciers able to retreat up to high altitudes where positive mass balance areas persist even under future warming scenarios.…”
Section: Mass Balance Sensitivity and Hysteresismentioning
confidence: 81%
“…However, long-term reconstructions using ice flow models are rare. Most existing quantitative modeling studies of GICs are restricted to timescales of decades (e.g., Leysinger-Vieli and Gudmundsson, 2004;Raper and Braithwaite, 2009) or centuries (Jouvet et al, 2009;Giesen and Oerlemans, 2010;Aðalgeirsdóttir et al, 2011;Zekollari et al, 2014;Zekollari and Huybrechts, 2015;Ziemen et al, 2016). Only a very limited number of studies exist for the longer timescales (e.g., Flowers et al, 2008;Laumann and Nesje, 2014).…”
mentioning
confidence: 99%
“…However, no clear trend in climate such as cooling or increased precipitation was found during this period to explain such a slowdown Ziemen et al, 2016). Field observations of the equilibrium line altitudes and surface mass balances on Lemon Creek and Taku glaciers (JIF) also do not support a slowdown (WGMS, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…A modeling study also found a negative mass balance for the entire JIF (−0.33 m w.e. a −1 ) for 1971-2010 (Ziemen et al, 2016). Their 40-year mass balance is a result of glacier mass stability until 1996 and rapid mass loss afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reanalysis climate products available for the region, including NCEP-NCAR, typically have coarse resolution that neither represents the complex topography of Alaska mountain ranges nor includes high-elevation weather station data (Lader and others, 2016). Together, these issues help explain our difficulty in reproducing point mass-balance observations and their associated balance gradients with our mass-balance modeling, as was also the case for recent modeling studies on Yakutat Glacier and the Juneau Icefield, both in Alaska (Trüssel and others, 2015;Ziemen and others, 2016). These challenges help us frame our discussion for monitoring recommendations for the future.…”
Section: Discussionmentioning
confidence: 74%